The Influence of Digital Reputation Management on the Success of Local Brands with Customer Trust as a Mediator - Ni Luh ketut Ayu Sudha Sucandrawati (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the influence of Digital Reputation Management (DRM) on the success of local brands with Customer Trust as a mediating variable. The research background departs from the increasing intensity of competition for local brands in the digital era that requires companies to strategically manage their reputation through credible content, online review management, and consistent digital interaction. The research method uses the Structural Equation Modeling – Partial Least Squares (SEM-PLS) approach with data processed from the results of a local brand consumer survey. The results of the study show that DRM has a significant positive effect on Customer Trust, and Customer Trust has a significant positive effect on the success of local brands. In addition, Customer Trust has proven to be an important mediator that bridges the relationship between DRM and local brand success. This research confirms that an effectively managed digital reputation not only impacts image enhancement, but also on the formation of trust which ultimately drives consumer loyalty and advocacy. These findings provide theoretical contributions to the digital marketing management literature as well as practical implications for local businesses in designing trust-based digital reputation strategies to strengthen brand competitiveness in the market.